Given that triangles \( \triangle JKL \) and \( \triangle PKQ \) are similar (denoted as \( \triangle JKL \sim \triangle PKQ \)), we can use the properties of similar triangles to find the length of segment \( KL \).
Let's denote:
- \( JK = 56 \) m
- \( KP = 14 \) m
- \( KQ = 21 \) m
- Let \( KL = x \)
Since the two triangles are similar, the corresponding sides are proportional:
\[ \frac{JK}{KP} = \frac{KL}{KQ} \]
Substituting the known lengths into the ratio gives:
\[ \frac{56}{14} = \frac{x}{21} \]
Calculating the left side:
\[ \frac{56}{14} = 4 \]
Thus, we have:
\[ 4 = \frac{x}{21} \]
To solve for \( x \), we can cross-multiply:
\[ 4 \cdot 21 = x \]
\[ 84 = x \]
Thus, the length of \( KL \) is:
\[ KL = 84 \text{ m} \]
Therefore, the correct answer is \( \text{84 m} \).